Rozwiąż równania 1.9 strona 105

Rozwiąż Równania 19 Strona 105 class=

Odpowiedź :

Odpowiedź:

[tex]a)\\\\(x-1)(x+6)-(x-2)^2=2(3x+4)\\\\x^2+6x-x-6-(x^2-4x+4)=6x+8\\\\x^2+5x-6-x^2+4x-4=6x+8\\\\9x-10=6x+8\\\\9x-6x=8+10\\\\3x=18\ \ |:3\\\\x=6\\\\\\b)\\\\x(2x+1)=4(x-2)+2(x+2)^2\\\\2x^2+x=4x-8+2(x^2+4x+4)\\\\2x^2+x=4x-8+2x^2+8x+8\\\\2x^2+x=12x+2x^2\\\\2x^2+x-12x-2x^2=0\\\\-11x=0\ \ |:(-11)\\\\x=0[/tex]

[tex]c)\\\\(7-2x)^2-(x+1)(x-5)=3(x-3)^2+3\\\\49-28x+4x^2-(x^2-5x+x-5)=3(x^2-6x+9)+3\\\\49-28x+4x^2-x^2+5x-x+5=3x^2-18x+27+3\\\\54-24x+3x^2=3x^2-18x+30\\\\-24x+3x^2-3x^2+18x=30-54\\\\-6x=-24\ \ |:(-6)\\\\x=4\\\\\\d)\\\\5(x+1)^2-3(x+4)^2-1=2(x+5)^2-6(7x+5)\\\\5(x^2+2x+1)-3(x^2+8x+16)-1=2(x^2+10x+25)-42x-30\\\\5x^2+10x+5-3x^2-24x-48-1=2x^2+20x+50-42x-30\\\\2x^2-14x-44=2x^2-22x+20\\\\2x^2-14x-2x^2+22x=20+44\\\\8x=64\ \ |:8\\\\x=8[/tex]

[tex]e)\\\\(3x-2)^2-(2x+1)^2=(2x+1)(2x-1)+x^2-12\\\\9x^2-12x+4-(4x^2+4x+1)=4x^2-1+x^2-12\\\\9x^2-12x+4-4x^2-4x-1=5x^2-13\\\\5x^2-16x+3=5x^2-13\\\\5x^2-16x-5x^2=-13-3\\\\-16x=-16\ \ |:(-16)\\\\x=1\\\\\\f)\\\\(2x-3)(2x+3)+5(x-1)^2=(3x-2)(3x-2)\\\\4x^2-9+5(x^2-2x+1)=(3x-2)^2\\\\4x^2-9+5x^2-10x+5=9x^2-12x+4\\\\9x^2-4-10x=9x^2-12x+4\\\\9x^2-10x-9x^2+12x=4+4\\\\2x=8\ \ |:2\\\\x=4[/tex]